Tertiary Education Funding at a Turning Point Using Marketing as an Effective Recovery Strategy - Stephen Delle Donpaala; Patricia Ayishetu Don (Research Parks Publishers, 2023)
The issue of tertiary education funding in Ghana and several other Sub-Saharan African countries are currently at a critical juncture. It is intriguing to consider the phenomenon of numerous students annually enrolling into diverse tertiary educational institutions and fulfilling their financial obligations. However, it is evident that these public entities persist in experiencing financial deficits in their administration of these educational institutions. Nonetheless, the matter concerning the allocation of funds for higher education is of utmost importance globally. The government is widely acknowledged to have a crucial role in the provision of financial support for tertiary education, both in developed and developing countries. It is also evident that universities and other higher institutions in Ghana acquire financial resources through the Internally Generated Fund (IGF), such as the school fees for both local fee-paying category and foreign students, Business Units such as Commercial Farms, Basic Schools, as well as local authority revenue from the numerous Metropolitan, Municipal, and District Assemblies (MMDAs) for specific university’s projects. Furthermore, the establishment of post-secondary education in Ghana has been facilitated by the active involvement of National and international institutions such as the Get-fund, Ford Foundation, the World Bank, and the Benedal Foundation. Based on the finding gathered, it was observed that the private tertiary education institutions in Ghana derived around 95% of their total revenue from tuition fees, while the remaining 5% was sourced through external channels. However, unlike their counterparts in public tertiary educational institutions with similarly large student populations, they do not experience financial shortfalls. This study investigates the origins and consequences of these losses with the aim of identifying a wise marketing approach that can be employed to recover and gain possible sustained financial independence from the public purse. The research methodology employed in this study involved the utilisation of secondary data sources to collect the necessary data for the purpose of formulating appropriate conclusions and recommendations. In sum, public tertiary institutions should, without deviating from their core mandate, identify their core strength, weaknesses, threats and take advantage of less costly opportunities prevailing at its doorsteps as a potential source of funding and also emphasis on academic quality assurance as a key branding tool in the higher education marketing mix. Hence, this article critically evaluates the current state of tertiary education funding, highlighting its importance and timeliness, and explores the potential benefits of utilising marketing as a viable tool for implementing a successful cost recovery strategy.